MNCs' R&D talent management in China: aligning practices with strategies - Wei, William Xiaojun; Li, Lydia Qianqian; Xin, Katherine; Pucik, Vlado (My University, 2019)
This paper aims to propose practical recommendations in accordance with the strategic roles played by research and development (R&D) in multinational companies (MNCs).
Keywords: talent management; R & D strategies; qualitative research; China